2000
DOI: 10.1128/jb.182.20.5864-5871.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Copper-Responsive Two-Component System on the Chromosome of Escherichia coli K-12

Abstract: Using a genetic screen we have identified two chromosomal genes, cusRS (ylcA ybcZ), from Escherichia coli K-12 that encode a two-component, signal transduction system that is responsive to copper ions. This regulatory system is required for copper-induced expression of pcoE, a plasmid-borne gene from the E. coli copper resistance operon pco. The closest homologs of CusR and CusS are plasmid-borne two-component systems that are also involved in metal responsive gene regulation: PcoR and PcoS from the pco operon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
320
1
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 311 publications
(332 citation statements)
references
References 40 publications
6
320
1
5
Order By: Relevance
“…The CusR/CusS system is predicted to monitor the periplasmic concentration of the metal ion, to modulate the expression of an RND-type copper efflux pump, encoded by the cusCFBA operon (Franke et al, 2003;Munson et al, 2000). Recently, it was shown that transcription of a second, uncharacterized, two-component system, encoded by the yedWV operon, is activated by copper ions in a CusR-dependent manner (Yamamoto & Ishihama, 2005), although its role in copper tolerance remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The CusR/CusS system is predicted to monitor the periplasmic concentration of the metal ion, to modulate the expression of an RND-type copper efflux pump, encoded by the cusCFBA operon (Franke et al, 2003;Munson et al, 2000). Recently, it was shown that transcription of a second, uncharacterized, two-component system, encoded by the yedWV operon, is activated by copper ions in a CusR-dependent manner (Yamamoto & Ishihama, 2005), although its role in copper tolerance remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the first copper-responsive regulatory system in the E. coli chromosome, a two-component signal transduction system designated Cu-sensing or cus locus, was identified (9). The cusRS genes form a sensor/regulator pair that activates the adjacent but divergently transcribed gene, cusC, and possibly two adjacent downstream genes, cusBA, in response to increasing copper.…”
mentioning
confidence: 99%
“…Mammalian systems require copper for many enzymes (4). Recently, new elements of copper homeostasis in bacteria have been identified, including transporters, multicopper oxidases, and two-component and MerR-like regulators (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%